2020
DOI: 10.1530/rep-19-0342
|View full text |Cite
|
Sign up to set email alerts
|

Necessity for LH in selection and continued growth of the bovine dominant follicle

Abstract: Previous research demonstrated that acute treatment with GnRH antagonist, Acyline, allowed follicle growth until ~8.5 mm and no dominant follicle was selected. This study evaluated whether deficient LH was the underlying mechanism for Acyline effects by replacing LH action, using human chorionic gonadotropin (hCG), during Acyline treatment. Holstein heifers (n = 24) during first follicular wave were evaluated by ultrasound and randomized into one of three treatments: Control (saline treatments), Acyline (5 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…The "freeze all" strategy in our study reduced the exposure of gametes and the endometrium to supraphysiological levels of progesterone (Yang et al, 2019). Another reason was that letrozole promotes the selection of dominant follicles, and embryos obtained from dominant follicles may be associated with improved implantation potential (Giorgetti et al, 1995;Hugues et al, 2005;Mermillod et al, 2008;Rosen et al, 2008;Gomez-Leon et al, 2020). Letrozole coadministration increases the secretion of LH by inhibiting the synthesis of oestrogen (Requena et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The "freeze all" strategy in our study reduced the exposure of gametes and the endometrium to supraphysiological levels of progesterone (Yang et al, 2019). Another reason was that letrozole promotes the selection of dominant follicles, and embryos obtained from dominant follicles may be associated with improved implantation potential (Giorgetti et al, 1995;Hugues et al, 2005;Mermillod et al, 2008;Rosen et al, 2008;Gomez-Leon et al, 2020). Letrozole coadministration increases the secretion of LH by inhibiting the synthesis of oestrogen (Requena et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Letrozole coadministration increases the secretion of LH by inhibiting the synthesis of oestrogen (Requena et al, 2008). Higher LH levels could probably advance the dominant follicle selection and drive growth of the dominant follicle after the beginning of diameter deviation (Hugues et al, 2005;Gomez-Leon et al, 2020). These fully developed preovulatory-stage follicles are more likely to yield high-quality oocytes (Rosen et al, 2008) and thus viable embryos (Mermillod et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the dominant follicle of all animals entered the regression phase by 72 hours after kisspeptin and GnRH antagonist treatment. A possible reason for the regression may be altered gene expression [47] and estradiol production by the dominant follicle [48] due to LH suppression [49].…”
Section: Plos Onementioning
confidence: 99%
“…Advanced puberty and maturity: In heifers the overall Dramatic increase in the absorption of trace minerals in the liver, heart, kidneys, spleen and lungs led to advance puberty and sexual maturity. Gomez-León et al (2020), Handcock et al (2020) mentioned increase in the hormone concentrations in the blood plasma and a high rate of BCS and weight are all factors that advance the age of puberty and sexual maturity in cows. Li et al (2019) reported the biofeedback episode causes the hypothalamus and thyroid gland to release a series of youth-promoting hormones such as growth hormone, estrogen and testosterone, as well as hormones that stimulate the adrenal gland and thyroid gland, leading lead to precocious puberty and sexual maturity.…”
Section: Hormone Concentrations (Fsh Lh Estrogen and Testosterone)mentioning
confidence: 99%